Optimisation of Cellulase Production by Penicillium funiculosum in a Stirred Tank Bioreactor Using Multivariate Response Surface Analysis. (25th June 2014) - de Albuquerque de Carvalho, Marcelle Lins; Carvalho, Daniele Fernandes; de Barros Gomes, Edelvio; Nobuyuki Maeda, Roberto; Melo Santa Anna, Lidia Maria; Castro, Aline Machado de; Pereira, Nei
Abstract : Increasing interest in the production of second-generation ethanol necessitates the low-cost production of enzymes from the cellulolytic complex (endoglucanases, exoglucanases, and β -glucosidases), which act synergistically in cellulose breakdown. The present work aimed to optimise a bioprocess to produce these biocatalysts from the fungus Penicillium funiculosum ATCC11797. A statistical full factorial design (FFD) was employed to determine the optimal conditions for cellulase production. The optimal composition of culture media using Avicel (10 g·L −1 ) as carbon source was determined to include urea (1.2 g·L −1 ), yeast extract (1.0 g·L −1 ), KH2 PO4 (6.0 g·L −1 ), and MgSO4 ·7H2 O (1.2 g·L −1 ). The growth process was performed in batches in a bioreactor. Using a different FFD strategy, the optimised bioreactor operational conditions of an agitation speed of 220 rpm and aeration rate of 0.6 vvm allowed the obtainment of an enzyme pool with activities of 508 U·L −1 for FPase, 9, 204 U·L −1 for endoglucanase, and 2, 395 U·L −1 for β -glucosidase. The sequential optimisation strategy was effective and afforded increased cellulase production in the order from 3.6 to 9.5 times higher than production using nonoptimised conditions.